Investigações sobre uma língua profissional: uma leitura discursiva de publicações na rede social LinkedIn - Quenzer, Viviane (2023)
This master's thesis focuses on understanding the discursive construction of a Top Voice's prescriptive publications on the normative use of the Portuguese language, produced and broadcast in a digital environment, more specifically on the professional social network LinkedIn. For our investigation, based on the regularities observed, we divided the posts into three scenographies: coach, trainer and self-help. All these posts are about writing and communication for the corporate environment. Our aim, based on the analysis of authorial productions on the web, is to reflect on (i) the influence of web 2.0 on the production of discourses, (ii) what language is being spoken about and (iii) the scenography used to disseminate this language. To do this, we draw on the theoretical and methodological writings of Dominique Maingueneau (2015), especially the notion of Scenes of Enunciation, with a focus on topical and non-topical units for the analytical path, and the concepts covered in the book Digital Discourse Analysis: a dictionary of forms and practices by Marie-Anne Paveau (2021) to describe the LinkedIn social network and how publications on this network work. We will also give a brief theoretical outline of the structuring concepts of Discourse Analysis from the book Discourse and Discourse Analysis by Dominique Maingueneau and Popular Linguistics by Marie-Anne Paveau in France and Roberto Leiser Baronas in Brazil, in order to begin to outline this interface between Discourse Analysis and Popular Linguistics in relation to our analysis material. For the analysis itself, we selected the business profile and 13 authorial publications of Dalva, elected in 2020 as LinkedIn's Top Voice. In conclusion, the work showed that the discourse on the cultured norm of the language, the one supported by grammars, takes on a new guise in the digital environment, on a social network that connects people with professional themes, and that, through a unique discursive production, that is, specific scenographies, allows this transposition to be advocated, building a different relationship from that of books, closer to the subjects, and that it is a different language, aimed at the corporate environment.